2010
DOI: 10.2308/aud.2010.29.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Conservatism after Enron

Abstract: SUMMARY: Corporate scandals and the resulting passage of the Sarbanes-Oxley Act (SOX) in 2002 significantly affected the auditing profession. The quality of financial statement audits was called into questioned and the media and regulators held audit firms responsible. Several studies found evidence of an increase in the issuance of going-concern opinions after the passage of SOX relative to earlier time periods (Geiger et al. 2005; Nogler 2008; Myers et al. 2008). Auditors, it appears, behave more conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 20 publications
7
66
0
4
Order By: Relevance
“…In addition, the existing studies are based on data from firms listed on the stock exchanges or on data contained in databases such as Compustat or CRSP (DeFond, Raghunandan, & Subramanyam, 2002;Feldmann & Read, 2010;Kaplan & Williams, 2012). These databases contain mostly listed firms, excluding smaller firms for their analysis, hence the importance of the need for future research to study unlisted firms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the existing studies are based on data from firms listed on the stock exchanges or on data contained in databases such as Compustat or CRSP (DeFond, Raghunandan, & Subramanyam, 2002;Feldmann & Read, 2010;Kaplan & Williams, 2012). These databases contain mostly listed firms, excluding smaller firms for their analysis, hence the importance of the need for future research to study unlisted firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are currently very few studies, either in Spain (Mareque, López-Corrales, & De Lima, 2012;Mareque, López-Corrales, & Pedrosa, 2011) or in other countries (Carson, Simnett, & Tronnes, 2011;Cheffers, Whalen, & Sielis, 2011;Cheffers, Whalen, & Thrun, 2010;Feldmann & Read, 2010;Jiang, 2013 and that show the effect of the financial crisis on audit reports. A recent review by Carson et al (2012) provides a synthesis of the existing academic literature on the presentation of reports containing problems of continuity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…studies have found that since the Sarbanes-Oxley Act (SOX) of 2002, auditors have been more likely to issue goingconcern opinions (Fargher and Jiang, 2008;Li, 2009;Feldmann and Read, 2010) which have been shown to reduce the risk of litigation (Mong and Roebuck, 2005). 10,11 We thus suppose that auditors are more likely to assign unfavorable audit opinions for companies involved in patent litigation when their perceived risk is affected by litigation disclosures.…”
Section: © 2017 Aess Publications All Rights Reservedmentioning
confidence: 99%
“…Li (2009) found that dependence at the firm level in the U.S. had no effect on going concern opinions before SOX; however, in 2003 dependence did make a difference. Later studies by Feldmann and Read (2010) and Kao, Li, and Zhang (2014) show that this change was only a temporary effect and that there is no effect in the longer term.…”
Section: Issue 2: Relative Size Of Fees and Dependencementioning
confidence: 99%